Radio Resource Allocation in Mobile Communication Systems - Husar, Andrej; Cepel, Peter; Brida, Peter; Wieser, Vladimir (Communications - Scientific letters of the University of Zilina, 2005)
In the article we deal with two types of Call Admission Control Schemes (Reservation-based CAC scheme and Probability-based CAC scheme) and we made simulations in Matlab environment. Both types of these transmission schemes belong to homogeneous type of radio resource management applications. Only voice application belongs here (traditional wireless networks) and each call demands the same amount of bandwidth (channel, frequency or time slots). Both schemes are compared and evaluated at the end of the article.